Review of the pros and cons when comparing high intensity interval training to moderate intensity continuous training - Elhamalawy, Ahmed (International Journal of Research in Medical Sciences, 2024)
High-intensity interval training (HIIT) has gained significant popularity in recent years as an effective exercise method for individuals seeking time-efficient workouts with substantial health benefits. For those leading busy lives, such as working professionals, engaging in regular physical activity holds pivotal importance. It serves as a catalyst for not only enhancing physical well-being but also nurturing mental health and boosting overall productivity. This review compares HIIT to traditional exercise to identify the advantages and disadvantages providing a valuable insight for healthcare professionals when educating patients on the matter.